Development of Written Communication Skills Through Creative Writing - level A1 - Maria SIMINA-SUCIU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Written communication skills are one of the most important parts of language learning, starting with level A1, the most important level, in our opinion, as this is where the language learning process begins. To develop this skill, students should write as many and as varied texts as possible. To this end, we would like to bring to your attention the creative writing method through which our students can practice writing texts. Although we refer to Romanian as a foreign language, these methods can be applied to any foreign language.